The l=2 stellarator with displaced helical windings - Kotenko, V.G.; Romanov, S.S.; Zalkind, V.M. (Вопросы атомной науки и техники, 2007)
The paper deals with the magnetic surface configuration properties in the frame of a new model of the l=2 stellarator with displaced helical windings. The displacement has been made to provide a better access to the plasma confinement volume. Numerical calculations have shown that the magnetic surface configuration, shifted inward the torus and appearing favorable for plasma confinement, can be realized in the absence of a transverse magnetic field. Проведено вивчення властивостей конфігурації магнітних поверхонь в новій моделі магнітної системи l=2 стеларатора зі зміщеними гвинтовими обмотками. Зміщення запроваджено з метою покращення доступу до об’єму утримання плазми. Показано, що найбільш сприятлива для утримання плазми зміщена в середину тора конфігурація магнітних поверхонь реалізується за відсутністю поперечного магнітного поля. Проведено изучение свойств конфигурации магнитных поверхностей в новой модели магнитной системы l=2 стелларатора со смещенными винтовыми обмотками. Смещение проведено с целью улучшения доступа к объему удержания плазмы. Показано, что благоприятная для удержания плазмы смещенная внутрь тора конфигурация магнитных поверхностей реализуется в отсутствие поперечного магнитного поля.